Isolation and characterization of Pyricularia oryzae isolated from lowland rice in Sarawak, Malaysian Borneo - Nor Ain, Hussin; Yeo, Freddy Kuok San; Nur Karimah, Mohamad; Nur Najwa, Hamsein; Vu, Thanh Tu Anh; Hung, Hui Chung; Lee, San Lai (Malaysian Society for Microbiology, 2020)
Aims: Rice blast disease caused by Pyricularia oryzae is one of the major biotic diseases of rice in Sarawak, Malaysian Borneo. This study aims to isolate and characterize rice blast fungus obtained from infected leaf collected from four different divisions in Sarawak, viz, Miri, Serian, Sri Aman, and Kuching. Methodology and results: Twelve succeeded isolates were pre-identified as P. oryzae by morphological characteristics of spores, followed by verification through (internal transcribed spacer) ITS sequencing. The isolates were evaluated for morphological characteristics, growth rate and sporulation rate, which were grown on two types of media, (filtered oatmeal agar) FOMA and (potato dextrose agar) PDA. Morphological characterization showed that the colony surface of the different isolates varied from smooth and fluffy to rough and flattened mycelia; some were with the present of concentric rings, and some with aerial mycelia. The growth rate and sporulation rate of each isolate varied based on types of media used. Most of the isolates grew faster on PDA than on FOMA but produced higher number of spores on FOMA as compared to PDA. Conclusion, significance and impact of study: This preliminary study showed that there were variations observed based on morphological and physiological characterization for the different isolates collected in Sarawak, Malaysian Borneo. This study is the first step towards understanding variation in the population of P. oryzae from Sarawak.